Hepatitis B virus infection and its prevention among the general Ghanaian population: Using the public health model of prevention approach - Senoo-Dogbey, Vivian E. (International Journal of Infection Control, 2021)
As a follow-up to the recently published Letter to the Editor in this journal titled ‘Hepatitis B infection and its prevention among healthcare workers in Ghana: More action required’ (1), I present in this current Letter as a discussion on hepatitis B virus (HBV) infection and its prevention among the general Ghanaian population.